In Silico Genome-Wide Analysis of the Pear (Pyrus bretschneideri) KNOX Family and the Functional Characterization of PbKNOX1, an Arabidopsis BREVIPEDICELLUS Orthologue Gene, Involved in Cell Wall and Lignin Biosynthesis - Cheng, Xi; Li, Manli; Abdullah, Muhammad; Li, Guohui; Zhang, Jingyun; Manzoor, Muhammad Aamir; Wang, Han; Jin, Qing; Jiang, Taoshan; Cai, Yongping; Li, Dahui; Lin, Yi (Frontiers in Genetics, 2019)
Stone cells are a characteristic trait of pear fruit, but the contents and sizes of stone cells negatively correlate with fruit texture and flavour. Secondary cell wall thickening and lignification have been established as key steps of stone cell development. KNOTTED-LIKE HOMEOBOX (KNOX) proteins play important roles in plant cell growth and development, including cell wall formation and lignification. Although the characteristics and biological functions of KNOX proteins have been investigated in other plants, this gene family has not been functionally characterized in pear. Eighteen PbKNOX genes were identified in the present study, and all of the identified family members contained the KNOX I and/or KNOX II domains. Based on the phylogenetic tree and chromosomal localization, the 18 PbKNOX genes were divided into five subfamilies [SHOOT MERISTEMLESS (STM)-like, BREVIPEDICELLUS (BP)-like, KNOTTED ARABIDOPSIS THALIANA 2/6 (KNAT2/6)-like, KNAT7-like, and KNAT3-5-like] and were distributed among 10 chromosomes. In addition, we identified 9, 11 and 11 KNOX genes in the genomes of grape, mei and strawberry, respectively, and the greatest number of collinear KNOX gene pairs formed between pears and peaches. Analyses of the spatiotemporal expression patterns showed that the tissue specificity of PbKNOX gene expression was not very significant and that the level of the PbKNOX1 transcript showed an opposite trend to the levels of stone cells and lignin accumulation. Furthermore, PbKNOX1 has high sequence identity and similarity with Arabidopsis BP. Compared with wild-type Arabidopsis, plants overexpressing PbKNOX1 not only showed an approximately 19% decrease in the secondary cell wall thickness of vessel cells but also exhibited an approximately 13% reduction in the lignin content of inflorescence stems. Moreover, the expression of several genes involved in lignin biosynthesis was downregulated in transgenic lines. Based on our results, PbKNOX1/BP participates in cell wall-thickening and lignin biosynthesis and represses the transcription of key structural genes involved in lignin synthesis, providing genetic evidence for the roles of KNOX in cell wall thickening and lignin biosynthesis in pear.